Financial Communication in Crisis Situations - Anatol Melega; Veronica Grosu; Corina Petrescu (Studies and Scientific Researches: Economics Edition)
Financial communication plays a key role in shaping stakeholders' decision-making processes, acquiring even greater importance in today's turbulent global landscape marked by various overlapping crises. Thus, the aim of the research revolves around a theoretical exploration, supported by a bibliometric analysis, to emphasize the intrinsic importance of financial communication. The research methodology is based on a bibliometric analysis of 3,000 scientific papers indexed in the Web of Science database, from 1975 to 2023, focusing on financial communication. To facilitate this analysis, specialized software tools for data processing and bibliometric exploration, namely VOSviewer and Bibliometrix, were used. The research findings underline the complexity and interdependence of the financial communication process in organizations, highlighting its evolution from transparency and reduction of information asymmetry in periods of stability, to the need for rapid adoption of digital technologies and integration of ESG dimensions during recent crises, all of which are essential to meet stakeholders' demands and maintain investors' trust.